Upaya Menumbuhkan Rasa Percaya Diri Anak Usia 5-6 Tahun melalui Media Boneka Jari - Nur Sa'adah; Masganti Sit (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
The purpose of this study is to improve self-confidence in children aged 5 to 6 years using finger puppet media. This study employs the Classroom Action Research (CAR) method based on the model by Kemmis and McTaggart. The study consists of two cycles, each comprising four stages: planning, implementation, observation, and reflection. Fifteen students from RA Al-Kautsar, aged five to six years, participated in this study. Data collection techniques included observation and documentation. Quantitative and qualitative methods were used in the data analysis. The findings indicate that children aged 5 to 6 years can benefit from the use of finger puppets to boost their self-confidence. Most children (34%) were classified as Not Yet Developed (NYD) in terms of self-confidence during the pre-cycle period. The average score increased to 63%, classified as Developing as Expected (DAE), following the intervention in the first cycle. The average percentage returned to the “Developing Very Well” (DVW) level of 92% in Cycle II. The children appeared more willing to perform in front of the class, were able to lead groups, and were more confident in expressing their opinions. Thus, finger puppets are an effective tool for fostering self-confidence in young children.